VEGF-C mediated enhancement of lymphatic drainage reduces intestinal inflammation by regulating IL-9/IL-17 balance and improving gut microbiota in experimental chronic colitis - Wang, Xiaolei (Am J Transl Res, 2017)
Background: Inflammation-associated lymphangiogenesis (IAL) induced by vascular endothelial growth factor (VEGF)-C/VEGF receptor-3 (VEGFR-3) pathway plays a crucial role in chronic intestinal inflammation. This study aimed to investigate the effects of VEGF-C mediated enhancement of lymphatic drainage on the intestinal inflammation in experimental chronic colitis (CC) and the potential mechanism was explored. Methods: Mouse CC model was established by three cycles of 2% DSS administration for 5 days following water administration for 5 days. CC mice were injected via the tail vein with AD-VEGF-C-EGFP (VEGF-C+DSS group) or AD-EGFP (AD-EGFP group) at the end of each cycle and animals in control group were given access to drinking water only. Disease activity index (DAI), lymphatic vessel density (LVD), colonic cytokines, Th9 cells (CD3(+) cells) and CD68(+) macrophage infiltration, and lymph flow were detected. Fresh feces were collected and processed for DNA extraction and MiSeq Illumina sequencing of V4 region of bacterial 16S rRNA gene. Alpha- and beta diversities and compositional differences at phylum and genus levels were determined in intestinal microbiota. Results: AD-VEGF-C treatment significantly reduced colon inflammation, elevated the increase in lymph drainage, decreased CD68(+) macrophages and CD3(+) T cells (Th9 cells), reduced IL-9, and increased IL-17 in colon mucosa when compared with DSS mice. In addition, VEGF-C treated mice showed significantly increased the abundance of Bacterioidate and decreased Firmicutes at phylum level in fecal samples. Conclusion: VEGF-C improves intestinal inflammation by enhancing lymphatic drainage, reducing intestinal Th9 cells, regulating intestinal IL-9/IL-17 balance and increasing intestinal Bacterioidate abundance in CC mice.